Psychiatric mental health nursing : concepts of care in evidence-based practice - Townsend, Mary C., 1941- 4 0 16; 5 (Philadelphia : F.A. Davis, 2006)
A guide to psychiatric mental health nursing that discusses basic concepts, foundations, therapeutic approaches, care of clients with alterations in psychosocial adaptation, and nursing for special populations. Includes CD-ROM with study aids.
Basic concepts in psychiatric/mental health nursing -- The concept of stress adaptation -- Mental health/mental illness: historical and theoretical concepts -- Foundations for psychiatric/mental health nursing -- Theoretical models of personality development -- Concepts of psychobiology -- Ethical and legal issues in psychiatric/mental health nursing -- Cultural concepts relevant to psychiatric/mental health nursing -- Therapeutic approaches in psychiatric nursing care -- Relationship development -- Therapeutic communication -- The nursing process in psychiatric/mental health nursing -- Therapeutic groups -- Intervention with families -- Milieu therapy: the therapeutic community -- Crisis intervention -- Relaxation therapy -- Assertiveness training -- Promoting self-esteem --Anger/agression management -- The suicidal client -- Behavior therapy -- Cognitive therapy -- Psychopharmacology -- Electroconvulsive therapy -- Complementary therapies -- Client education -- Nursing care of clients with alterations in psychosocial adaptation -- Disorders usually first diagnosed in infancy, childhood, or adolescence -- Delirium, dementia, and amnestic disorders -- Substance-related disorders -- Schizophrenia and other psychotic disorders -- Mood disorders -- Anxiety disorders -- Somatoform and sleep disorders -- Dissociative disorders -- Sexual and gender identity disorders -- Eating disorders -- Adjustment and impulse control disorders -- Psychological factors affectingmedical conditions -- Personality disorders -- Psychiatric /mental health nursing of special populations -- The aging individual -- The individual with HIV disease -- Problems related to abuse or neglect -- Men's and women's health issues -- Community mental health nursing -- Psychiatric home nursing care -- Forensic nursing -- The bereaved individual.
Includes bibliographical references and index.
Adult;Adult
System requirements for accompanying CD-ROM: PC Pentium II or higher ; OS Windows 98/ME/2000/XP.
Keywords: 2 -- 0; 6; methods.;nursing.;methods. -- Psychiatric nursing.;Psychiatric nursing.;Nursing.;Psychiatric Nursing;Evidence-Based Medicine.;Mental Disorders;Psychotherapy; 20; 2